Recurrent Macular Edema in Central Retinal Vein Occlusion Treated with Intravitreal Ranibizumab using a Modified Treat and Extend Regimen - Dirani, A.; Mantel, I.; Ambresin, A. (Klinische Monatsblätter für Augenheilkunde, 2015)
Background: The aim of this study was to evaluate the stability over time of the individually defined interval of intravitreal ranibizumab injection (IVR) for the treatment of recurrent macular edema (ME) in central retinal vein occlusion (CRVO). Patients and Methods: A case series of treatment naïve patients followed in the Jules Gonin Eye Hospital for macular edema due to central retinal vein occlusion is presented. Patients were treated monthly with IVR until complete absence of fluid on qualitative SD-OCT with a minimum of 5 monthly IVR. Thereafter, they were followed according to a modified treat and extend regimen (mTER). Results: Twelve eyes (12 patients) with ME due to CRVO were included. The mean follow-up period was 31.3 months. Analysis showed that best corrected visual acuity (BCVA), central macular thickness and qualitative spectral domain optical coherence tomography (SD-OCT) showed comparable results under monthly interval, after titration of an individualized interval and when performed in a series. 78 % of treating intervals were within ± 2 weeks of the first individually adjusted interval. The mean first defined interval was 4.3 weeks and the mean interval over time was 5.5 weeks (p = 0.003). There was a trend towards longer interval over time. Conclusion: The adjusted interval of retreatment of patients with ME due to CRVO showed a high stability with a trend toward longer duration over time. An mTER regimen seems to be valuable to follow patients with ME with good stabilization of VA.
Keywords: Zentralvenenverschluss; Makulaödem; modifiziertes treat and extend (mTER) Schema; intravitreale Injektionen; Ranibizumab